Hubungan Lama Menderita Hipertensi Dengan Tingkat Kecemasan Pada Lansia Di Desa Praon Nusukan Surakarta - Laksita, Indra Dwi, Arum Pratiwi , S.Kp., M.Kes (2016)
This study aimed to determine the relationship long suffered from hypertension at the level of anxiety in the elderly in the village Praon Nusukan Surakarta. This type of research was descriptive analytic study. The subjects were elderly people who come in and have a history of hypertension and was listed as a resident of the village Praon Nusukan Surakarta. This type of research was an analytic description of the study design with cross sectional approach. Data collection methods used were questionnaires and documentation. The sample was 38 elderly people who had hypertension and recorded as villagers Praon Nusukan Surakarta by sampling using accidental purposive sampling. Analyzed using Spearman rank. The results of this study showed that the number of respondents with hypertension age less than 7 years are not worried as much as 20 people. The number of respondents with hypertension age less than 7 years old with anxiety 2 people. The number of respondents with hypertension long time more than 7 years are not worried as much as 2 people. The number of respondents with hypertension long time more than 7 years as many as 14 people anxious. Data analysis technique conducted with correlative. Value Spearman's rho between old hypertension and anxiety scores are known for 0749 with the 0.01 value which is less than 0.05. The results showed that there was no significant relationship between duration of hypertension and anxiety level. The longer the respondents had hypertension, the higher the level of anxiety felt by respondents.